Introduction of an innovative method to the field of education in Uzbekistan (Journal of Universal Science Research, 2023)
In this article, you will find examples of the methods and changes introduced by our great teachers in the performance of the instrument. You will get information about the high skills, experiences and innovations of major professional musicians and teachers.